Effect of Sintering Temperature and Duration on the Formation of Single-Phase Pb0.9Bi0.1Fe0.55Nb0.45O3 Solid Solution. Issue 3 (2nd July 2016) - Dadami, Sunanda T.; Matteppanavar, Shidaling; Shivaraja, I.; Rayaprol, Sudhindra; Murugendrappa, M. V.; Angadi, Basavaraj
ABSTRACT: Effect of sintering temperature and duration on single phase formation and structural properties of Pb0.9 Bi0.1 Fe0.55 Nb0.45 O3 (PBFNO) solid solution was investigated. The single step solid state reaction method was adopted to achieve the pure perovskite phase. Calcination was carried out at 700 o C for 2 h and sintering at different temperatures as 800 o, 850 o, 900 o, 950 o, 1000 o and 1050 o C for 1 h and also at 800 o C for 1-5 h to achieve the single phase in PBFNO solid solution. From the X-ray diffraction studies, it was found that sintering at 800 o C for 3 h was optimum for achieving single phase and all the other conditions showed an impurity phase. Rietveld refinement was carried out on single phase PBFNO solid solution by using FullProf Suite, which confirmed the monoclinic structure with Cm space group and the obtained refinement parameters were Rp =15.7; Rw p =20.7, Rexp =16.72, χ 2 (Chi 2 )=1.54. The lattice parameters were: a=5.666(3) Å, b=5.667(4) Å, c=4.017(2) Å and α=γ=90 o, β=89.943(4) o . Scanning electron micrograph showed an average grain size of ∼2 μm with uniform morphology. All the results clearly revealed the significance of low temperature and short duration sintering to control the single phase in PBFNO solid solution. GRAPHICAL ABSTRACT: